CRIF counteracts oncogenic Ras and regulates heterochromatin. - Lim, S.J.; Li, J.; Li, W.X. (Molecular Genetics and Genomics, 2025)
Oncogenic Ras mutations are prevalent in human cancers, yet the mechanisms by which Ras promotes tumorigenesis remain incompletely understood. In Drosophila, oncogenic Ras (Ras[V12]) induces tissue overgrowth and metastasis, but the cellular restraints it must overcome are unclear. We have identified Drosophila CRIF, the homolog of mammalian CR6-interacting factor 1 (CRIF1), as a modifier of Ras[V12]-induced lethality and Ras[V12]-induced overgrowth and cell proliferation. Knockdown of CRIF exacerbated Ras[V12] phenotypes, while CRIF overexpression ameliorated them. Further, we found that CRIF was also required for heterochromatin formation, as loss of CRIF suppressed position-effect variegation (PEV) and reduced the levels of Heterochromatin Proteins 1 (HP1) and Histone H3 Lysine 9 trimethylation (H3K9me3). CRIF physically interacted with HP1, suggesting a role in recruiting HP1 to heterochromatin. Notably, CRIF did not regulate HP1 transcription or total protein levels but influenced HP1 localization. Our findings demonstrate that CRIF functions as a tumor suppressor by negatively regulating cell proliferation and maintaining heterochromatin stability. CRIF's interaction with HP1 and its role in heterochromatin regulation suggest a novel mechanism linking heterochromatin to tumor suppression in Ras-driven cancers. These results highlight CRIF as a potential therapeutic target and provide new insights into the interplay between chromatin regulation and oncogenic signaling.